SUMOylation inhibitors synergize with FXR agonists in combating liver fibrosis - Jiyu Zhou; Shuang Cui; Qingxian He; Yitong Guo; Xiaojie Pan; Pengfei Zhang; Ningning Huang; Chaoliang Ge; Guangji Wang; Frank J. Gonzalez; Hong Wang; Haiping Hao (Nature Communications)
Abstract Farnesoid X receptor (FXR) is a promising target for nonalcoholic steatohepatitis (NASH) and fibrosis. Although various FXR agonists have shown anti-fibrotic effects in diverse preclinical animal models, the response rate and efficacies in clinical trials were not optimum. Here we report that prophylactic but not therapeutic administration of obeticholic acid (OCA) prevents hepatic stellate cell (HSC) activation and fibrogenesis. Activated HSCs show limited response to OCA and other FXR agonists due to enhanced FXR SUMOylation. SUMOylation inhibitors rescue FXR signaling and thereby increasing the efficacy of OCA against HSC activation and fibrosis. FXR upregulates Perilipin-1, a direct target gene of FXR, to stabilize lipid droplets and thereby prevent HSC activation. Therapeutic coadministration of OCA and SUMOylation inhibitors drastically impedes liver fibrosis induced by CCl4, bile duct ligation, and more importantly NASH. In conclusion, we propose a promising therapeutic approach by combining SUMOylation inhibitors and FXR agonists for liver fibrosis.